Low bone mineral density is associated with an elevated risk of developing increased arterial stiffness: A 10-year follow-up of Japanese women from the Japanese Population-based Osteoporosis (JPOS) cohort study. (January 2019) - Jaalkhorol, Myadagmaa; Fujita, Yuki; Kouda, Katsuyasu; Tamaki, Junko; Komatsu, Misa; DongMei, Namiraa; Sato, Yuho; Tachiki, Takahiro; Yura, Akiko; Kajita, Etsuko; Kagamimori, Sadanobu; Iki, Masayuki
Highlights: Elevated brachial-ankle pulse wave velocity (a measure of arterial stiffness) is associated with an increased risk of cardiovascular disease. In our study of 446 women Japanese women aged ≥50 years, 37.2% developed increased arterial stiffness over the 10 years of follow-up. Low bone mineral density was associated with increased arterial stiffness. Women with low bone mineral density should be examined for cardiovascular disease. Abstract: Objective: Only a few longitudinal studies have assessed the relationship between bone mineral density (BMD) and arteriosclerosis. This study aimed to determine whether low BMD at baseline is associated with the development of increased arterial stiffness, as evaluated by brachial-ankle pulse wave velocity (baPWV), in Japanese women. Methods: A baPWV value of ≥1800 cm/s was adopted as the criterion for increased arterial stiffness, i.e., the outcome of the study. Of the 725 women aged ≥50 years who completed the baseline survey, we excluded the 166 who already met this criterion. Of the remaining women, we analyzed data from the 446 who completed at least one of the follow-up surveys conducted 5 or 10 years after baseline. BMD at the lumbar spine (LS) and total hip (TH) was measured by dual-energy X-ray absorptiometry in the baseline survey. baPWV was measured both at baseline and at follow-up. Multivariate logistic regression was used to evaluate the independent effect of BMD at baseline on developing the outcome during 10-year follow-up. Results: We identified 166 women who newly developed increased arterial stiffness. The odds ratios (OR) for a 1 SD decrease in BMD at LS and TH for developing the outcome were 1.20 (95% confidence interval [CI]: 0.91–1.50), and 1.44 (95% CI: 1.14–1.81), respectively, after adjusting for age and systolic blood pressure. After additionally adjusting for baPWV at baseline, the OR for a 1 SD decrease in BMD at TH remained significant (1.33, 95% CI: 1.02–1.72). Conclusion: Low BMD at TH was significantly associated with the development of increased arterial stiffness during a 10-year follow-up of Japanese women.